2007
DOI: 10.1245/s10434-007-9520-7
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Adrenalectomy for Isolated Adrenal Metastasis

Abstract: LA is equivalent to OA in terms of margin status, local recurrence, disease-free interval and overall survival. LA for metastatic adrenal lesions is safe, with equivalent long-term oncological outcomes providing the additional benefits of a minimally invasive technique. LA can be recommended as an appropriate initial approach for isolated adrenal metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
135
1
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 196 publications
(164 citation statements)
references
References 18 publications
23
135
1
5
Order By: Relevance
“…The mathematical model introduced with the stepwise regression (backward procedure) considering the three chosen independent variables together (diameter of the metastasis and pre-adrenalectomy DFI, suggested by the literature as independent factors of prolonged survival (3)(4)(5), and post-adrenalectomy DFI, individuated by the univariate analysis as the factor mostly related to survival in our sample ) was not significant (P=n.s.). Then at step1 the model excluded the less significant variable (diameter of the metastasis), and the new p value for the remaining two was: P=0.04.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…The mathematical model introduced with the stepwise regression (backward procedure) considering the three chosen independent variables together (diameter of the metastasis and pre-adrenalectomy DFI, suggested by the literature as independent factors of prolonged survival (3)(4)(5), and post-adrenalectomy DFI, individuated by the univariate analysis as the factor mostly related to survival in our sample ) was not significant (P=n.s.). Then at step1 the model excluded the less significant variable (diameter of the metastasis), and the new p value for the remaining two was: P=0.04.…”
Section: Resultsmentioning
confidence: 75%
“…When compared to open adrenalectomy, LA for AM results in less morbidity (including pain), shorter hospital stay, quicker recovery and better cosmetic results (that is all the benefits of laparoscopic approach), with the same oncologic outcomes (2,5,26,29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic adrenalectomy has been shown to improve patients' morbidity and to reduce hospitalization with a comparative oncological outcome compared to the open resection technique. 13 However, laparoscopic procedures are contraindicated in lesions larger than 6 cm. 14 Overall, the rate of major complication after surgery is around 1.8%.…”
Section: Introductionmentioning
confidence: 99%
“…Long-term survival rates have been reported in patients after adrenalectomy due to metastatic disease, provided there was an isolated metastasis [3,[11][12][13]. In terms of surgical approach, numerous authors have reported safety and similar oncological results of laparoscopic adrenalectomy for metastases compared to open surgery [11,12,[14][15][16]. In the present study, we have presented our clinical results from the endoscopic removal of suspected adrenal metastases, and have tried to evaluate the significance of certain clinical and pathological parameters for prediction of long-term survival after adrenalectomy.…”
Section: Introductionmentioning
confidence: 99%